Implementasi Zero Food Waste di SDN Ekologi Kahuripan Padjajaran Melalui Biokonversi Maggot: Kolaborasi Mahasiswa UPI Bersama TPS 3R Ciseureuh - Nenden Permas Hikmatunisa; Alfi Nasthi Fauziah; Delia Apriliani; Dinda Nurainun Fazrin; Dwi Maulidawanti; Ica Nurlaela; Khalishah Nurul Salamah; Uni Nurnikmah (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2025)
Food waste is a global issue that continues to be discussed. This is because the problem of food waste can have an impact on the environment, health and climate. Through the Sustainable Development Goals (SDGs) initiative, creating a sustainable community through food waste management is made a top priority. This article discusses the implementation of the Zero Food Waste program at SDN Ekologi Kahuripan Padjajaran using the Black Soldier Fly (BSF) maggot bioconversion approach. This community service was carried out by P3K UPI Purwakarta students who collaborated with TPS 3R Ciseureuh Purwakarta to manage food waste. This service activity is carried out through several stages which include preparation, implementation and evaluation, involving students and their parents in managing organic waste. The results of bioconversion are maggots and organic fertilizer which will be used into products with economic value. This program has succeeded in increasing environmental awareness, reducing food waste, and can create sustainable solutions in managing organic waste. It is hoped that this article can make recommendations for implementing similar methods in other areas as an environmentally friendly waste management model.